Three dimensional analysis of low cycle fatigue failure in engine part subjected to multi-axial variable amplitude thermo-mechanical load. (April 2016) - Sharifi, Seyed Mohammad Hossein; Saeidi Googarchin, Hamed; Forouzesh, Farinaz
Abstract: During the E5 engine durability test, the failure happens in cast iron cylinder head. This is characterized as low cycle fatigue. The macro-scale cracks initiate and propagate in valve bridge region. The present investigation focuses on simulating durability test and evaluating low cycle fatigue life of the failed part. The simulation includes one pre-step as a determination of material grid and three steps as fluid, structural and fatigue analyses. In order to cover the durability test, the analysis steps are repeated at five crack speeds, 750, 1650, 2075, 2350, and 2600 rpm. The cylinder head is subjected to cyclic multi-axial variable amplitude loads. In fatigue analysis, critical plane and cumulative damage theories are utilized in order to predict fatigue life. A general script is developed and validated so as to calculate fatigue life in the whole model. The numerical results also show that the failure of critical cylinder head can be characterized as low cycle fatigue. The valve bridge region, in which high temperature exists during engine operation, is the critical area in fatigue analysis approach. The simulation results are in a good agreement with the durability test observations. Highlights: Low cycle fatigue failure occurs in valve bridge region of cylinder head. Critical cylinder head subjected to E5 engine durability test is simulated. Numerical and Experimental results are in a good agreement. Graphical life prediction avoids misunderstanding about structural fatigue behavior. It can provide helpful viewpoints for designers.